Rescuing macrophage normal function in spinal cord injury with embryonic stem cell conditioned media. Issue 1 (December 2016) - Guo, Lei; Rolfe, Alyssa; Wang, Xi; Tai, Wenjiao; Cheng, Zhijian; Cao, Kai; Chen, Xiaoming; Xu, Yunsheng; Sun, Dongming; Li, Jinhua; He, Xijing; Young, Wise; et al.
Abstract Background Macrophages play an important role in the inflammatory responses involved with spinal cord injury (SCI). We have previously demonstrated that infiltrated bone marrow-derived macrophages (BMDMs) engulf myelin debris, forming myelin-laden macrophages (mye-Mϕ). These mye-Mϕ promote disease progression through their pro-inflammatory phenotype, enhanced neurotoxicity, and impaired phagocytic capacity for apoptotic cells. We thus hypothesize that the excessive accumulation of mye-Mϕ is the root of secondary injury, and that targeting mye-Mϕ represents an efficient strategy to improve the local inflammatory microenvironment in injured spinal cords and to further motor neuron function recovery. In this study, we administer murine embryonic stem cell conditioned media (ESC-M) as a cell-free stem cell based therapy to treat a mouse model of SCI. Results We showed that BMDMs, but not microglial cells, engulf myelin debris generated at the injury site. Phagocytosis of myelin debris leads to the formation of mye-Mϕ in the injured spinal cord, which are surrounded by activated microglia cells. These mye-Mϕ are pro-inflammatory and lose the normal macrophage phagocytic capacity for apoptotic cells. We therefore focus on how to trigger lipid efflux from mye-Mϕ and thus restore their function. Using ESC-M as an immune modulating treatment for inflammatory damage after SCI, we rescued mye-Mϕ function and improved functional locomotor recovery. ESC-M treatment on mye-Mϕ resulted in improved exocytosis of internalized lipids and a normal capacity for apoptotic cell phagocytosis. Furthermore, when ESC-M was administered intraperitoneally after SCI, animals exhibited significant improvements in locomotor recovery. Examination of spinal cords of the ESC-M treated mice revealed similar improvements in macrophage function as well as a shift towards a more anti-inflammatory environment at the lesion and parenchyma. Conclusions The embryonic stem cell conditioned media can be used as an effective treatment for SCI to resolve inflammation and improve functional recovery while circumventing the complications involved in whole cell transplantation.